Pitfalls of Extensive Documentation in the Emergency Department - Blome, Andrea (Ochsner J, 2020)
Background: The law mandates careful record-keeping in the emergency department, and clinical imperatives also support the value of complete and legible reports. A common assumption is that extensive documentation increases the yield of relative value units (RVUs) and higher levels of care, thereby maximizing reimbursement. However, overdocumentation presents certain risks, possibly impacts physician efficiency, and does not ensure that records are more readable and clinically useful. We examined the effect of increased documentation on actual reimbursement. Methods: We conducted a 12-month productivity analysis of patients per hour (pt/h), RVUs per hour (RVU/h), amounts of monies billed, and amounts of monies collected for all full-time supervising physicians in a university emergency medicine training program. Results: RVU/h vs pt/h yielded a positive linear relationship (R(2)=0.7571) and a strong correlation coefficient of 0.87. RVU/h vs revenue collection (amount actually paid) yielded a moderately positive linear relationship (R(2)=0.1752), with a correlation coefficient of 0.42. The relationship between pt/h and collections was weak (R(2)=0.0815), with a correlation coefficient of 0.29. A quartile comparison showed an inflection point, suggesting that after the third quartile, RVU/h did not appear to help generate significantly higher collections. Conclusion: The data, while not definitive, suggest that overly extensive documentation may increase RVU totals but, after a point, does not reliably increase revenue generation.